Design and Build a Cooperative Management Information System in Savings and Loan Cooperatives: Rancang Bangun Sistem Informasi Pengelolahan Koperasi Pada Koperasi Simpan Pinjam - Sari, Anika; Rosyid, Mochammad Alfan (Universitas Muhammadiyah Sidoarjo, 2022)
Cooperative is a business entity whose members are individuals or legal entities, cooperatives based on their activities based on the cooperative principle as well as a people's economic movement based on the principle of kinship. Ar-Rohman Savings and Loans Cooperative (KSP) is a cooperative engaged in the savings and loan sector, this cooperative has been operating since 2016 which is located in the village of the temple ban Sidoarjo. In general, Ar-Rohman Savings and Loans Cooperative has several problems. Among them are managers that still use books, take more time, and have more energy in managing them, and the absence of information technology in cooperative management. The method used in this research is the waterfall method and software as follows: Sublime Text as an editor, PHP programming language, Code Igniter framework, Apache web server and MySQL database. This research will produce a web-based cooperative management information system in the ar-rohman savings and loan cooperative which can assist in managing the Ar-Rohman Savings and Loan Cooperative efficiently, computerized, and as a cooperative archive storage facility.